The Role and Protection of Laws to Notary Related To the Dispute That Made Between the Parties - Monicha Rossalia Adigita; Umar Ma’ruf; Aryani Witasari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study to determine and analyze: 1) Factors leading to disputes between the parties relating to the deed of Notary. 2) Role of relevant Notary Deed had made in the event of a dispute between the parties. 3) The legal protection against related Notary Deed which is made in the event of a dispute between the parties. Legally sociological research approach. The data in this study are primary data obtained from the field by means of interviews and secondary data consists of primary legal materials, secondary law and tertiary legal materials by means of literature. Data were then analyzed qualitatively.Based on the results of data analysis can be concluded that: 1) Factors leading to disputes between the parties relating to Deed, there are two reasons, namely: breach of contract committed by one of the parties which resulted in the loss and not the acquisition of rights of one party and if the deed made by Notary goes wrong in terms of formal and material aspects of birth. 2) The role of the Notary in the event of any dispute if the dispute caused by the parties themselves then the Notary will not be involved and would only be called as a witness in the trial, but if notaries who made a mistake in making the deed of the Notary may be sued by the parties which would result be under the hand and null and void. The parties will also get compensation if the parties feel aggrieved by deed made by Notary. 3) Protection of the Notary Law contained in Article 66 of Law No. 2 2014 On Notary, wherein if the investigators, prosecutors and judges will perform a calling and examination of the Notary, must go through the approval of the Honorary Council of Notaries.Keywords: Role and Legal Protection; Notarial Deed; Dispute